PELATIHAN AKUPRESURE UNTUK KESEHATAN IBU DAN ANAK SEBAGAI UPAYA PENCEGAHAN STUNTING DI DESA KREMBUNG KECAMATAN KREMBUNG - Anik Latifah; Desta Ayu Cahya Rosyida; Yuni Khoirul Waroh; Setiawandari Setiawandari; Sumiati Sumiati (Jurnal LENTERA, 2022)
Growth is a quantitative change, namely by increasing the number, size, dimensions ofcells, organs and individuals. Currently, Indonesia still has nutritional problems, one ofwhich is stunting or short stature. Conditions in Indonesia based on data from the Studyon the Nutritional Status of Toddlers in Indonesia (SSGBI) 2019 are still relatively high,where the prevalence of stunting is 27.67%. In June 2022, a survey and data collection ofchildren under five in Krembung Village, Krembung District, Sidoarjo Regency wasconducted to obtain data on 20 toddlers experiencing stunting. This Community Serviceaims to improve the knowledge and skills of posyandu mothers in Krembung Village,Krembung District, Sidoarjo Regency regarding Optimizing Toddlers with Baby Massage.Initial Community Service activities carried out field surveys, licensing, implementationand evaluation. One form of community service is the efforts of the midwifery studyprogram, architecture, science and health, by carrying out activities in the communitythat are beneficial, one of which is massage as a form of community service. Activitiesare carried out once a week. presenting baby massage treatment is the best and cheapest form of alternative treatment in an effort to increase baby's weight optimally.So it is necessary to use the utilization carried out by the baby's mother.